Chile´s National Adaptation Plan to Climate Change of the forestry and agricultural sector. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
CCAFS informed the Chilean National Climate Change Adaptation Plan for forestry and agriculture on climate services and gender-responsive climate smart agriculture (CSA).